Experimental investigation of coherent Smith–Purcell radiation from a "flat" grating - Aryshev A.; Kalinin B.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Bardai R.; Ishkhanov B.; Shvedunov V. (2005, 2005)
Title screen